Changing bodies, changing meanings : studies on the human body in antiquity - Montserrat, Dominic, 1964- (London ; New York : Routledge, 1998)
This beautifully illustrated book is the first to place at its centre the emotional and experiential aspect of the body in antiquity.
Introduction / Dominic Montserrat -- pt. 1. Perfect bodies, imperfect bodies: Disabling bodies / Nicholas Vlahogiannis. The dynamics of beauty in classical Greece / Richard Hawley -- pt. 2. Bodies and signs in Latin literature: Exuvias effigiemque : Dido, Aeneas and the body as sign / Angus Bowie. Bodies in flux : Ovid's Metamorphoses / Penelope Murray -- pt. 3. Modifying the early Christian body: Bodies and blood : Late Antique debate on martyrdom, virginity and resurrection / Gillian Clark. Reading the disjointed body in Coptic : from physical modification to textual fragmentation / Terry Wilfong -- pt. 4. The ancient body's trajectory through time: The irresistible body and the seduction of archaeology / Lynn Meskell. Unidentified human remains : mummies and the erotics of biography / Dominic Montserrat. Nacktleben / Jane Stevenson.
Includes bibliographical references (pages 213-226) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Human body in literature; Human body -- History -- Social aspects; Literature, Ancient -- History and criticism; Corps humain dans la littérature.; Corps humain -- Histoire -- Aspect social; Littérature ancienne -- Histoire et critique; TRAVEL -- Special Interest -- Literary; LITERARY CRITICISM -- General; Human body in literature; Human body -- Social aspects; Literature, Ancient; Electronic books; Criticism, interpretation, etc; History